Flow velocity records at rock glacier Outer Hochebenkar (Äußeres Hochebenkar), 2024 - Martin Stocker-Waldhuber; Bernd Seiser; Lea Hartl; Giulia Bertolotti; Andreas Gschwentner; Andrea Fischer (PANGAEA, 2025)
Surface velocities have been regularly monitored at the rock glacier in Outer Hochebenkar, Ötztal Alps, Austria since the early 1950s. This data collection provides annual coordinates of the stones at each cross profile since 1997, when the time series was restarted at the initial profile positions as well as in 2021. Additional coordinates are provided from stones at the longitudinal profile along the centre flow line since 2011. These data-series is a continuation of Hartl et al. (2016). Coordinate System: MGI Austria GK West (EPSG: 31254).
In: Stocker-Waldhuber, Martin; Fischer, Andrea; Hartl, Lea; Abermann, Jakob; Schneider, Heralt (2021): Flow velocity records at Rock Glacier Outer Hochebenkar (Äußeres Hochebenkar), Ötztal, Tyrolian Alps, Austria, 1997 et seq [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.928244